STEAM-DESIGN PROCESS WITH TELESCOPE PROJECT TO FOSTER STUDENTS’S ATTITUDE TOWARD SCIENCE - Jihan Reihana Nurfadhila; Nanang Winarno; Eka Cahya Prima; Ahmad, Nur Jahan (INSECTA: Integrative Science Education and Teaching Activity Journal, 2025)
Attitude Toward Science in the PISA global ranking shows a low-average. This study analyzed the effect of STEAM-Design Process on students’ attitude toward science in the topic of optical instruments. Quantitative research method alongside a quasi-experimental design was utilized in this study. The experimental class used the STEAM-Design Process whereas the control group used conventional learning. The sample for this study were 8th-grade students from a public school in Tasikmalaya Regency, Indonesia. The experimental group consisted of 38 students, while the control group consisted of 30 students. Students ages ranged from 13-14 years old. The data obtained in this study used 60 statements form a questionnaire with two open-ended questions. The findings revealed a significant difference in attitude toward science between the experiment and control class. The N-Gain score in the experiment class is 0.32 and control class 0.12, which is described as medium and low improvement. Based on this research, teaching through STEAM- Design Process is effective approach that can be significantly improve attitude toward science. Educators should consider integrating this model more broadly in secondary science curricula. It is recommended to explore the long-term effects and explore ways to better support the emotional dimensions of student attitudes.